Analysis of g s-transferase, protien tyrosine phosphatase 1B, nuclear factor kappa-B1 and leptin receptor genetic polymorphisms as risk factors for Malaysian type 2 diabetes mellitus subjects - Etemad, Ali (2013)
Type Two Diabetes Mellitus (T2DM) is one of the serious chronic diseases which are associated with Cardiovascular Disease (CVD) and its complexity though; make it as one of the main mortality contributing factors. The deceive factors such as age, gender,ethnics, lifestyle, genetic backgrounds and their combinations with the environment play an important role in the development of T2DM. The International Diabetes Federation (IDF) predicted the portion of people with Diabetes Mellitus in the world would rise from 285 million in 2010 to 439 million in 2030. The prevalence of T2DM among Malaysian adults was 8.3% a decade ago and became 14.9% in 2009; more dramatically,newly diagnosed T2DM was 1.8% and rose to 5.4% at the same time. In 2011, the sam trend were observed where overall diabetes, known diabetes and newly diagnosed diabetes increased to 21.5%, 11% and 10% for respectively. In the human genome, several genes were reported as functional candidate genes for T2DM and its associated disease such as CVD, which have intense effects on metabolism, oxidative stress, enzymatic activity and inflammatory expression; genetic variation within these molecules could determine the insulin resistance or leptin regulation and directly increased the risk of T2DM and its complications. The main objective of this study was to determine the association of genetic polymorphisms of Glutathion S-Transferase (GST), Protein Tyrosine Phosphatase 1B (PTP1B), Nuclear Factor Kappa-B1 (NFK-B1) and Leptin Receptor (LEPR) genes in Malaysian T2DM subjects in comparison with healthy individuals. These genes are also known as positional and functional candidate gene which has association with insulin signaling/resistance and modulate its expression followed by altering the inflammation in different tissues. This research was approved by the Ethical Committee of National Heart Institute (IJNEC/05/10 (02)) and Faculty of Medicine and Health Sciences,Universiti Putra Malaysia (JSB_Mac (12)02). A total of 587 subjects were approached initially; among them 565 volunteers were recruited for this study. Based on the International Diabetes Federation (IDF) criteria, a total of 284T2DM subjects and 281 healthy individuals as control subjects were recruited under this study. The socio-demographic and other details were recorded using the questionnaire. Genomic DNA was extracted from the blood and buccal cells using commercially available kits. Biochemical analyses were done for the lipid profiles in both subjects. Polymerase chain reaction (PCR), Multiplex-PCR, Restriction Fragment Length Polymorphism PCR-RFLP methods were used to determine the genetic polymorphisms of the respective genes in all the subjects. The PCR products were separated and analyzed by agarose and polyacrylamide gel electrophoresis. Genotypes were confirmed by DNA sequencing and the banding patterns. The statistical analyses were conducted after exclusion of outliers and the normal values were evaluated by general linear model package through the SPSS statistical software. The overall allele frequency varies from (P= 0.0494) in PTP1B-Pro303Pro to (P= 1) in PTP1B-Pro387Leu. The maximum chi-square belongs to GST loci with four polymorphisms (P= 1620.97) and the minimum (P= 13.3) observed for IVS6+G82A polymorphism. There was a significant difference between T2DM subjects and healthy individuals in PTP1B-IVS6+G82A polymorphism (P=0.007) followed by LEPR–Gln223Agr polymorphism (P= 0.011). Also, the anthropomorphic values differed significantly (P≤0.01) for age (P= 0.000), Body Mass Index (BMI) (P= 0.014) and Waist Hip Ratio (WHR) (P= 0.000). The fasting plasma glucose (P= 0.000) and HbA1C (P= 0.000) was two critical values for diabetes identification which were significantly different between T2DM and control subjects. The Systolic Blood Pressure (SBP) (P=0.048), cardiovascular risk (P= 0.014), Family history of diabetes (P= 0.007) and blood lipid patterns significantly differed between T2DM subjects and healthy individuals which included High Density Lipoprotein (HDL) (P= 0.000), Triglyceride (TG) (P=0.001) and total Cholesterol (P= 0.003). However, the LDL levels of T2DM subjects was under control and not significantly different (P=0.060) with healthy individuals. The association studies and their evaluation based on the Pearson correlation values were conducted in three different categories. There was not a significant correlation among the selected polymorphisms but for lifestyle patterns, there was a significant and a negative/indirect Pearson value for age versus sex and exercise (r= –0.153 and –0.121) respectively and positive/direct correlation with T2DM symptoms (r= 0.327). Also, there was a direct association between the gender and smoking or alcohol consumption (r=0.381 and 0.305) respectively and negative association with symptoms (r= –0.113). There was a direct correlation between Smoking/Alcohol and BMI/Symptom (r= 0.290 and 0.154) respectively followed by indirect correlation between exercise and diabetes subjects (r= –0.117). The association of the blood lipid patterns was evaluated which was direct and positive between cholesterol and LDL, HDL, TG and Chol/HDL ratio (r=0.851, 0.304, 0.268 and 0.489) respectively. But, there was a negative association between HDL and TG and Chol/HDL ratio (r= –0.244 and –0.574) respectively. There was a direct correlation between FPG and TG and HbA1C (r= 0.283 and 0.732) respectively followed by (r= 0.091 and 0.226) for HbA1C and Chol/HDL ratio respectively versus TG levels. Finally, there was an indirect correlation between FPG and LDL (r= –0.103) followed by direct association between LDL levels and Chol/HLD ratio (r= 0.563). In conclusion, the diabetes risk factors with the impact of PTP1B-IVS6+G82A polymorphism [age (P= 0.002), FPG (P= 0.000), HbA1C (P= 0.000), LDL (P= 0.012) and family history (P= 0.010)] and LEPR-Gln223Agr polymorphism [age (P= 0.022), WHR (P= 0.000), FPG (P= 0.000), (P= 0.000), LDL (P= 0.000), HDL (P= 0.000) Chol (P=0.010) and family history (P=0.000)] were significantly different between the case and control subjects. This observation could help particularly in case of early diagnoses for the subjects who have the same genotypic pattern and prevent the diabetes and its complications in high risk categories. The findings from this research indicated that the genetic polymorphisms [IVS6+G82A (P=0.007) and Gln223Agr (P=0.011)] of genes (PTP1B and LEPR) respectively were significant between T2DM patients and healthy individuals. This information can be considered as risk factors for the development of T2DM in Malaysian subjects. Apart from that, (BMI, WHR, SBP, HDL, TG, Cholesterol, CVD Risk and family history) were also associated between T2DM and control subjects. It is obviously important to create a database for predicting the risk factors in the Malaysian population in early future which needed a comprehensive data included the environmental factors versus the genetic background and the community attitudes with the prediction of probable epigenetic modifications.